ANALYSIS OF EDITORIAL TEXT TEACHING MATERIALS TO IMPROVE STUDENTS' WRITING SKILLS - Rully Silvia; Euis Eti Rohaeti (JLER (Journal of Language Education Research), 2022)
This study is to analyze the editorial text teaching materials used by teachers in schools. In addition, to determine the ability of students in compiling editorial texts. The research method used is descriptive qualitative. The research subjects were 5 teachers as experts and users of teaching materials in textbooks. There were 98 students as respondents to find out the ability to write editorial texts and the benefits of using textbooks as a learning guide. Based on the results of the study, it was explained that 80% of teachers use textbooks in each lesson because they greatly help students' understanding. The use of reading texts in textbooks 60% of teachers said they were less contextual or in accordance with the needs of students. The order of the percentage of input from the teacher towards editorial text teaching materials in the textbook is 80% in the presentation, 80% of the content of the material, 60% of the reading text, 40% of the design and 20% of the mechanical elements. The results of the research from students stated that editorial text teaching materials helped student learning. The presentation of teaching materials from textbooks greatly affects students' understanding and ability to write editorial texts. From the results of the students' editorial text writing, 20% were able to compose it well, 30% of students could compile a text only needed to be guided first by the teacher, and 50% of students had not been able to compile an editorial text because they were confused with the chosen idea and the development of the writing.